Peranan Komponen Fisik dalam Meningkatkan Kemampuan Servis Tenis: Analisis Power Lengan, Koordinasi Mata-Tangan, dan Kekuatan Otot Tungkai - Ians Aprilo; Poppy Elisano Arfanda; M. Adam Mappaompo (Departement of Mathematics Education, 2024)
The tennis serve is a critical aspect of gameplay, requiring both technical skill and physical fitness. This study investigates the impact of three physical components arm power, hand-eye coordination, and leg muscle strength on the performance of tennis serves. Using a correlational research design, data were collected from 20 beginner tennis players aged 16–18 years in Makassar Arm power was measured through a medicine ball throw test, hand-eye coordination via the hand wall toss test, and leg muscle strength using a leg dynamometer. The Hewitt Tennis Achievement Test was employed to evaluate serve accuracy and consistency. The findings reveal that all three physical components significantly influence service performance (p < 0.05). Arm power enhances ball speed, hand-eye coordination improves serve accuracy, and leg muscle strength supports stability and energy transfer during the serve motion. Combined, these factors explain a significant proportion of variance in service effectiveness. This study emphasizes the need for comprehensive training programs focusing on these physical attributes to improve serve performance among beginner tennis players. These results provide actionable insights for coaches and athletes aiming to optimize serve efficiency, highlighting the interplay between strength, coordination, and stability as foundational elements of successful tennis serve.